Approaches to risk–benefit assessment of seafood consumption: lessons learned from an evidence scan - Santillana Farakos, Sofia M.; Heilman, Jacqueline; Abt, Eileen; Dennis, Sherri (Frontiers in Nutrition, 2024)
Qualitative and quantitative risk-benefit assessments (RBA) can be used to support public health decisions in food safety. We conducted an evidence scan to understand the state of the science regarding RBA in seafood to help inform seafood dietary advice in the United States. We collected published RBA studies assessing seafood consumption, designed inclusion and exclusion criteria to screen these studies, and conducted systematic data extraction for the relevant studies published since 2019. Our findings indicate the selection of health risks and benefits does not generally follow a systematic approach. Uncertainty and variability in RBAs is often not addressed, and quantitative RBAs making use of a single health metric generally have not been leveraged to directly support published regulatory decisions or dietary guidance. To elevate the role of RBA in supporting regulatory decision-making, risk assessors and risk managers must work together to set expectations and goals. We identified the need for a prioritization phase (e.g. multicriteria decision analysis model) to determine the risks and benefits of greatest public health impact to inform the RBA design. This prioritization would consider not only the degree of public health impact of each risk and benefit, but also the potential for risks and benefits to converge on common health outcomes and their importance to subpopulations. Including a prioritization could improve the utility of the RBAs to better inform risk management decisions and advance public health. Our work serves to guide the United States Food and Drug Administration's approaches to RBA in foods.